Generation of a nodal line and Weyl points by magnetization reorientation in Co3Sn2S2 - F. Schilberth; M.-C. Jiang; F. Le Mardelé; L. B. Papp; I. Mohelsky; M. A. Kassem; Y. Tabata; T. Waki; H. Nakamura; G.-Y. Guo; M. Orlita; R. Arita; et al. (npj Quantum Materials)
Abstract Topological magnets exhibit fascinating physics like topologically protected surface states and anomalous transport. Although these states and phenomena are expected to strongly depend on the magnetic order, their experimental manipulation has been scarcely studied. Here, we demonstrate the magnetic field control of the topological band structure in Co3Sn2S2 by magneto-optical spectroscopy. We resolve a magnetic field-induced redshift of the nodal loop resonance as the magnetization is rotated into the kagome plane. Our material-specific theory, capturing the observed field-induced spectral reconstruction, reveals the emergence of a gapless nodal loop for one of the in-plane magnetization directions. The calculations show that the additionally created Weyl points for in-plane fields marginally contribute to the optical response. These findings demonstrate that breaking underlying crystal symmetries with external fields provides an efficient way to manipulate topological band features. Moreover, our results highlight the potential of low-energy magneto-optical spectroscopy in probing variations of quantum geometry.